In vitro assessment of antifungal activity of cinnamon leaves extract against the Colletotrichum sp. causes of anthracnose on tomato - Sudirga, Sang Ketut; Darmadi, Anak Agung Ketut; Yulihastuti, Dwi Ariani; Wijaya, I Made Saka (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Tomato is a horticultural plant widely cultivated in Bali. Over the three years, the productivity and quality of this plant have tended to decrease due to pathogen-derived diseases, such as anthracnose caused by Colletotrichum sp. Until recently, control of this pathogenic fungus has relied on chemical-based fungicides, which lead to many long-term complications, including pathogen resistance, environmental pollution, the extinction of non-target microorganisms, and negative impacts on human health. Therefore, alternative methods for plant disease control are urgently needed to combat these pathogen attacks. The use of plant-derived active compounds has been intensively researched worldwide as a more environmentally friendly alternative. The main objective of this research was to investigate the effectiveness of Cinnamomum burmanii acetone extract in inhibiting the growth of Colletotrichum sp., the causative agent of anthracnose in tomatoes, through an in vitro approach. A non-factorial randomized complete design was applied in the experiment. The results showed that the crude extract of cinnamon leaves inhibited the growth of the Colletotrichum sp. with an MIC value of 0.9%, an inhibition zone of 2.55 mm, and an optimal inhibitory concentration of 2%, producing an inhibition zone of 11.10 mm. A GC-MS analysis was conducted to identify the active compounds in the cinnamon leaf extract. Sixteen active compounds were identified, nine of which are known to have antimicrobial activity.